Evaluation of Vienna’s World Economic Position Based on Global and World City Rankings - Andrea Uszkai (DETUROPE)
Metropolitan areas play a dominant role in today’s economic, social and environmental processes; therefore the scientific interest has also increased related to the global and world cities. They can be considered as key players of the world economy and a very complex competition takes place among them, which crosses the national state borders. Every city tries to reach the most favorable position and this rivalry has helped the birth of several city rankings. This paper has two important aims. Firstly, it explains the term of the world and global city based on the international literature and it is also looking for the answer, whether the Austrian capital belongs to which category. Secondly, it examines the position of Vienna in the different world and global city rankings.